2019
DOI: 10.1007/s12035-019-01713-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Induced Cell Survival Is Dependent on TRPM7 Expression and Function

Abstract: Mg 2+ homeostasis is essential for cell survival and the loss of this regulation has been associated with many neurodegenerative diseases, including loss of dopaminergic neurons. Although the neurotoxin-mediated loss of dopaminergic neurons in Parkinson disease models is extensively studied, the ion channel(s) that regulate Mg 2+ homeostasis and thus could prevent neuronal cell death is not yet identified. Here, we show that TRPM7 (transient receptor potential melastatin 7) is involved in regulating Mg 2+ home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
2
25
0
2
Order By: Relevance
“…Importantly, the decrease in TRPM7 expression was specific, since no change in actin levels were observed upon neurotoxintreatment. Consistent with these studies a decrease in TRPM7 expression has also been shown in PD patients and in the samples from neurotoxin-induced substantia nigra pars compacta regions (Sun et al, 2019), which further suggests that loss of TRPM7 could lead to neurodegeneration. Similarly, mutations in TRPM7 has been reported in some familial PD patients (Hermosura et al, 2005), and although the expression and/or function of TRPM7 was not identified in this study, a decrease in TRPM7 expression and/or function could be the reason for the observed neuronal loss.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Importantly, the decrease in TRPM7 expression was specific, since no change in actin levels were observed upon neurotoxintreatment. Consistent with these studies a decrease in TRPM7 expression has also been shown in PD patients and in the samples from neurotoxin-induced substantia nigra pars compacta regions (Sun et al, 2019), which further suggests that loss of TRPM7 could lead to neurodegeneration. Similarly, mutations in TRPM7 has been reported in some familial PD patients (Hermosura et al, 2005), and although the expression and/or function of TRPM7 was not identified in this study, a decrease in TRPM7 expression and/or function could be the reason for the observed neuronal loss.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, TRPM7 mutants in zebrafish have decreased DA neurons (Decker et al, 2014), suggesting that changes in the Mg 2+ influx could induce neurodegeneration. Consistent with this observation, decreased Mg 2+ intake induced DA neuron loss, whereas Mg 2+ supplementation prevented neurotoxin-mediated decrease in DA neurons (Oyanagi and Hashimoto, 2011;Sun et al, 2019). These results suggest that TRPM7-mediated regulation of intracellular Mg 2+ could promote neuronal survival, however, its regulation, specifically TRPM7 activation in DA cells is not fully identified.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations